Characterisation of signal amplitude-frequency for indoor power line communication channel in the 1 - 30 MHz broadband frequencies - Ajibade, Adedayo Oluyomi (Array, 2021)
The transmission of data signals over power lines is a very promising technique for delivering indoor broadband communication services. However, since power grids were originally designed for high-voltage low-frequency signal transmission, there is a frequency mismatch between the power grid and high-frequency data signals. This mismatch poses a challenge to deploying power lines as a communication channel. Although, studies and researches conducted in several countries have made transmission of data over power lines possible, the behaviour and properties of the power grid cannot be generalised. Hence, the need for in-depth experiment and measurement on the suitability and capability of the Nigerian power grid for data transmission is crucial for proper characterising and modelling of the power line communication (PLC) channel. In this paper, we present experimental measurements and results of the effects of frequency variations on the attenuation experienced by broadband high-speed data signals transmitted over the Nigerian indoor power line network.